MicroRNA-24 antagonism prevents renal ischemia reperfusion injury - Lorenzen, Johan M; Kaucsar, Tamas; Schauerte, Celina; Schmitt, Roland; Rong, Song; Hübner, Anika; Scherf, Kristian; Fiedler, Jan; Martino, Filippo; Kumarswamy, Regalla; Kölling, Malte; Sörensen, Inga; et al. (Journal of the American Society of Nephrology, 2014)
Ischemia-reperfusion (I/R) injury of the kidney is a major cause of AKI. MicroRNAs (miRs) are powerful regulators of various diseases. We investigated the role of apoptosis-associated miR-24 in renal I/R injury. miR-24 was upregulated in the kidney after I/R injury of mice and in patients after kidney transplantation. Cell-sorting experiments revealed a specific miR-24 enrichment in renal endothelial and tubular epithelial cells after I/R induction. In vitro, anoxia/hypoxia induced an enrichment of miR-24 in endothelial and tubular epithelial cells. Transient overexpression of miR-24 alone induced apoptosis and altered functional parameters in these cells, whereas silencing of miR-24 ameliorated apoptotic responses and rescued functional parameters in hypoxic conditions. miR-24 effects were mediated through regulation of H2A histone family, member X, and heme oxygenase 1, which were experimentally validated as direct miR-24 targets through luciferase reporter assays. In vitro, adenoviral overexpression of miR-24 targets lacking miR-24 binding sites along with miR-24 precursors rescued various functional parameters in endothelial and tubular epithelial cells. In vivo, silencing of miR-24 in mice before I/R injury resulted in a significant improvement in survival and kidney function, a reduction of apoptosis, improved histologic tubular epithelial injury, and less infiltration of inflammatory cells. miR-24 also regulated heme oxygenase 1 and H2A histone family, member X, in vivo. Overall, these results indicate miR-24 promotes renal ischemic injury by stimulating apoptosis in endothelial and tubular epithelial cell. Therefore, miR-24 inhibition may be a promising future therapeutic option in the treatment of patients with ischemic AKI.